Methodology of synchronization among strategy and operation. A standards-based modeling approach (2017)
Enterprise Architecture (EA) has gained importance in recent years, mainly for its concept of “alignment” between the strategic and operational levels of organizations. Such alignment occurs when Information Technology (IT) is applied correctly and timely, working in synergy and harmony with strategy and the operation to achieve mutually their own goals and satisfy the organizational needs.Both the strategic and operational levels have standards that help model elements necessary to obtain desired results. In this sense, BMM and BPMN were selected because both have the support of OMG and they are fairly well known for modelling the strategic level and operational level, respectively. In addition, i* modeling goal can be used for reducing the gap between these two standards. This proposal may help both the high-level design of the information system and to the appropriate identification of the business processes that will support it.This paper presents a methodology for aligning strategy and the operation based on standards and heuristics. We have made a classification for elements of the models and, for some specific cases, an extension of the heuristics associated between them. This allows us to propose methodology, which uses above-mentioned standards and combines mappings, transformations and actions to be considered in the alignment process.